2019
DOI: 10.1080/14763141.2019.1601250
|View full text |Cite
|
Sign up to set email alerts
|

The effect of uphill and downhill slopes on centre of pressure movement, alignment and shot outcome in mid-handicap golfers

Abstract: The aim of the study was to examine changes in centre of pressure (COP) movement, alignment and shot outcome during golf shots from flat, uphill, and downhill slopes by midhandicap golfers. Twelve male golfers hit balls with a six-iron from the flat and 5° slopes while kinematics and kinetics of the swing were collected. A launch monitor measured performance outcomes. A shift in the centre of pressure was found during the backswing when playing on a slope, but disappeared during the downswing. Golfers attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(50 reference statements)
0
2
1
Order By: Relevance
“…And the ball speed decreased by an average of 1.3% and 4%, respectively [ 34 ] did a similar study and found that as the ground inclination increases, the carry distance, the vertical launch angle of the ball, and the flying height of the ball decrease. Unlike our study, the results of Hiley et al showed no statistical difference in ball speed and hitting distance between the three slopes [ 24 ]. The reason may be that they studied a slope of 5 , Smaller slopes may have less effect on hitting parameters.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…And the ball speed decreased by an average of 1.3% and 4%, respectively [ 34 ] did a similar study and found that as the ground inclination increases, the carry distance, the vertical launch angle of the ball, and the flying height of the ball decrease. Unlike our study, the results of Hiley et al showed no statistical difference in ball speed and hitting distance between the three slopes [ 24 ]. The reason may be that they studied a slope of 5 , Smaller slopes may have less effect on hitting parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…On the left and right axis, on the downhill slope moves the center of gravity to the left by 22% more than on the flat slope. Both Blenkinsop et al [ 23 ] and Hiley et al [ 24 ] studied changes in center of pressure (COP) motion and shot outcomes when golfers play golf from flat, uphill, and downhill slopes. The results all found that the slope had an effect on the change in the center of pressure during the full swing, but the speed of the ball was not affected.…”
Section: Introductionmentioning
confidence: 99%
“…Centre of pressure (COP) can be described as the point at which force from the feet is applied to the ground, meaning ground reaction forces (GRFs) act through this point also. Blenkinsop et al 3 and Hiley et al 4 published the first scientific papers on sloping lies, investigating the effect of uphill and downhill lies on COP movement, alignment and shot outcome in low 3 and mid 4 handicap golfers. They found that the golfers exhibited the same pattern of COP movement as described by Ball and Best, 5 where the COP starts slightly towards the front foot at address before moving toward the back foot during the backswing, and quickly shifting to the front foot in the downswing, with most golfers having their COP close to their front foot through ball contact.…”
Section: Centre Of Pressure Patterns and Ground Reaction Forcesmentioning
confidence: 99%